ANALISIS KELEMBAGAAN BADAN STANDARDISASI INSTRUMEN LINGKUNGAN HIDUP DAN KEHUTANAN: SEBUAH KENISCAYAAN - Subarudi Subarudi (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2023)
The Agency for Standardization of Environment and Forestry Instruments-ASEFI (Badan Standardisasi Instrumen Lingkungan Hidup dan Kehutanan-BSILHK) as a planner, formulator, and implementor of environment and forestry is still facing handicaps in implementing its tasks and function. This needs an institutional analysis in an effort to solve its problems..This research aims to analyze the institutional aspect of ASEFI focusing on regulation, organization structure and working mechanism, human resources and financial support. The research approach used is a content analysis and descriptive qualitative methods. Research results revealed that policy and regulation that support the implementation of the task and function of ASEFI is relatively adequate and can be a guide in its operational pattern. The nomenclature of ASEFI and its technical implementation unit is still needed for further improvement and its working mechanism must be enhanced both inside and outside of the Ministry of Environment and Forestry. Priority programs should be conducted in a short-term period in the fulfillment of standardization analyst both in quality and quantity sides. Besides that, the legal financial source of ASEFI has not clear yet, so that it should be determined with its exact financial sources. There are six important steps to be done by ASEFI for improving its main tasks so that its performance could be improved significantly in the near future.